Plant poisoning in Thailand: A 10-year analysis from Ramathibodi poison center - Charuwan Sriapha (2018)
© 2015, SEAMEO TROPMED Network. All rights reserved. Plant poisoning is not uncommon in Thailand. The objective of this study was to determine the incidence, type, clinical manifestations, severity and outcomes of plant poisoned patients in Thailand over a 10-year period. We retrospectively reviewed data from the Ramathibodi Poison Center Toxic Exposure Surveillance System for 2001-2010. A total of 2,901 poisonous plant exposure cases were identified, comprising 3.1% of the 92,392 poison cases recorded during the study period. This was the fifth most common type of poisoning recorded. Children aged <13 years comprised the largest percent (69.8%) of the cases. The major type of exposure was unintentional ingestion. Ninety-nine types of poisonous plants were recorded as the causative agents among 99.1%of the cases. Gastrointestinal symptoms were reported in 72.0% of cases with Jatropha curcas (physic nut) comprising 54.1% of these. Most patients had only minor signs and symptoms. The mortality rate among the total plant poisoning cases was 0.9%, with 26 deaths. Thirteen deaths occurred in children aged <13 years. The greatest number of fatalities were due to ingestion of Manihot esculenta (cassava), primarily due to multi-system organ failure. Children aged <13 years are at the greatest risk for plant poisoning in Thailand; mostly unintentional. Most cases were minor and the mortality rate was low. Jatropha curcas was the most common cause of poisoning and Manihot esculenta was the most common cause of death. Public education is important to minimize these poisonings.